Dampahinga a coconut development and farm resort complex in Marinduque - Labay, Francine Mae L. (College of Architecture, University of the Philippines Diliman, 2025)
Agriculture and tourism are pivotal sectors that drive employment and economic growth in the Philippines. Agritourism integrates these industries to enhance rural quality of life and boost local economies through sustainable agricultural practices. Despite its significance, this sector is still underutilized in the local context. Marinduque, an island rich in culture and natural resources, remains largely unexplored. Its abundance in coconut presents an opportunity that can be leveraged for ventures that would provide additional income for local farmers. This comprehensive design project seeks to boost the agritourism potential of Marinduque by employing architectural strategies that creates a balance between development and environmental conservation through a farm resort complex. Guided by the principles of experiential architecture, the design product translates qualitative analyses into a tangible facility that streamlines the coconut farming processes in Marinduque, while crafting an engaging and immersive experience for its prospective tourists.